Tanggungan Nafkah Suami yang Digantikan Istri menurut Ulama Pedesaan - Madiha Dzakiyyah Chairunnisa; Icep Baban Abdul Wahab; Lilis Nurasiah Jamil (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2021)
Running married life, of course between husband and wife have rights and obligations of each that must be fulfilled. The duty of the husband is to give dowries and livelihood to the wife. while the obligation of the wife who is the husband's right is a wife must obey and obey the husband. In addition, the wife is also required to meet all the needs of the husband, both spiritual and spiritual needs. However, among the community there are many problems of role as if exchanged, the wife who feeds the husband with the reasons husband is no longer able to work due to illness, also because the husband is reluctant to work. Reality is much happening among the people of Sindangjaya Village. This attracted the attention of researchers to find out more, how the opinion of the village cleric Sindangjaya towards providing a loving wife to her husband.